INVESTIGASI KESEHATAN PERBANKAN MENGGUNAKAN METODE RGEC DAMPAKNYA TERHADAP PROFITABILITAS - Syahrul, Syahrul; Sjahruddin, Herman; Hamiddin, Muhammad Irwan Nur; Syar, Alimuddin (Universitas Riau Kepulauan, 2025)
The success of a financial institution, such as a bank, in carrying out its operational activities can be seen through its health level measured by the RGEC method (risk profile, good corporate governance, earning, and capital) and its impact on profitability proxied by return on assets (ROA).The assessment of a bank's health not only serves as an indicator of financial stability but also acts as a signal of trust for investors and stakeholders. This quantitative research aims to investigate the impact of RGEC on ROA at Bank Sulselbar for the 2014-2023 period, using total sampling technique, with 40 financial statements analyzed using multiple linear regression through Eviews-13 software. The investigation results show that RGEC, measured by a low risk profile and earnings in its implementation, can indeed increase the bank's profitability, while good corporate governance, which has been well implemented, proves to have a significant influence in explaining profitability. In the final test, high capital was found not to increase the bank's profitability